ANALISA KECEPATAN MOTOR PADA ALAT BANTU PENGELASAN BAHAN LEHER KNALPOT STAINLESS STEEL - Murod, Moh Iqbal; Sakti, Arya Mahendra (Jurnal Rekayasa Mesin, 2022)
In the manufacturing process, especially welding an object, there are still several obstacles, namely the quality of the welding results, besides depending on the welding work process it also depends on the selection of predetermined welding parameters so that the results obtained are very good. Therefore, every difference in welding speed is different as well as the results produced. So with the "stainless steel exhaust neck welding tool" it is hoped that it can help the welding process activities on the stainless steel exhaust neck. In the process, this tool still needs to be tested in terms that most affect the quality and productivity at rotational speed, it is necessary to carry out further studies related to this research. Therefore, the authors are interested in analyzing the variations in motor speed on the welding results on the tool. One way to analyze the welding results is to perform a tensile test for pipe welding with a diameter of 24mm and a thickness variation of 1mm and 1.2m, with variations in the welding speed of 3,4,5 mm/second. After getting the welding results, a tensile test is carried out to determine whether or not variations in motor speed are affected and to determine the maximum ability of the specimen to withstand loads which is commonly referred to as "Ultimate Tensile Strength" (UTS). From the tensile tests carried out, there was a decrease in the average value of the tensile stress for stainless steel pipe welding at a speed variation of 3 mm/second by 59.11 kg/mm2 to 53.53 kg/mm2 at a speed variation of 4 mm/second, as well as speed variation of 5mm/second which has an average tensile stress value of 45.13 kg/mm2. In other words, the variation of the welding speed of 3 mm/second is the ideal welding speed variation when the welding process uses a stainless steell exhaust neck.